2007
DOI: 10.1677/joe-06-0024
|View full text |Cite
|
Sign up to set email alerts
|

Local cytokine levels associated with delayed-type hypersensitivity responses: modulation by gender, ovariectomy, and estrogen replacement

Abstract: It is well established that females mount stronger immune responses than males, but only very little is understood about the underlying mechanisms. We have analyzed local cytokine differences among intact females, those that had been ovariectomized (OVX), those receiving estrogen replacement after OVX, and males, both before and after production of delayed-type hypersensitivity (DTH) responses. We report confirmation of a much larger DTH response in females versus males. However, OVX resulted in an even larger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 48 publications
3
19
1
1
Order By: Relevance
“…This is in contrast to older animals (12 weeks) where we [29] and others [reviewed in 30] have demonstrated a more robust response in females. Nursing by a sensitized dam did not just accelerate this gender difference because nursing also resulted in suppression of the response in the males.…”
Section: Discussioncontrasting
confidence: 96%
“…This is in contrast to older animals (12 weeks) where we [29] and others [reviewed in 30] have demonstrated a more robust response in females. Nursing by a sensitized dam did not just accelerate this gender difference because nursing also resulted in suppression of the response in the males.…”
Section: Discussioncontrasting
confidence: 96%
“…The mechanism for the suppressive effects of E2 on DTH is not clear, but E2 is not believed to directly affect T cells in DTH as female severe combined immunodeficient (SCID) mice reconstituted with thymocytes from E2-treated mice did not show a decrease in the DTH response (Taube et al, 1998). Instead, the E2-mediated inhibition of DTH is believed to involve a decrease in the antigen presentation to T cells and an alteration of the cytokine pattern (Salem et al, 2000;Ma et al, 2007). Similarly, E2 treatment reduces the ability of splenic DCs to present antigen to T cells and to produce proinflammatory cytokines in other inflammatory models (Liu et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, evidence that some milk immune cells can pass from the milk across the wall of the gastrointestinal tract and into the neonate has accumulated. This occurs in a variety of species, including rats [18,19], sheep [18,20], pigs [21], baboons [22], and mice [23,24,25]. While many of these studies used concentrated cells and delivery by gavage, others have demonstrated the movement of cells into the neonate under entirely physiological conditions, and gone on to demonstrate that these cells affected subsequent immune responses in the recipients when adult [25,26].…”
Section: Introductionmentioning
confidence: 99%